2007
DOI: 10.1111/j.1530-0277.2007.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen Blocks Expression and Sensitization of Anxiety‐Like Behavior in an Animal Model of Repeated Stress and Ethanol Withdrawal

Abstract: Background-Repeated exposures to forced ethanol diets (EDs) or restraint stress sensitize anxiety-like behavior during a future ethanol withdrawal. The present investigation assessed whether pretreatment of rats with agents targeting receptor systems thought to be important in treating relapse in alcoholic patients would prevent sensitization of anxiety-like behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 73 publications
(120 reference statements)
2
58
0
Order By: Relevance
“…Withdrawal symptoms after repeated administration of GHB have been described in baboons (Weerts et al 2005), rats (Bania et al 2003) and humans (LeTourneau et al 2008) and the present data extend these findings to suggest a withdrawal syndrome after ten daily injections of 500 mg/kg GHB to rats. The increased social anxiety seen after abrupt discontinuation of GHB treatment is reminiscent of that seen in rats undergoing either ethanol (Knapp et al 2007) or benzodiazepine (File et al 1991) withdrawal, and consistent with there being some similarity in the neuroadaptations caused by these compounds on brain GABAergic systems. Interestingly, this withdrawal effect was not seen in rats given the MDMA/GHB combination, suggesting an amelioration of acute GHB withdrawal when coadministered with MDMA.…”
Section: Discussionmentioning
confidence: 65%
“…Withdrawal symptoms after repeated administration of GHB have been described in baboons (Weerts et al 2005), rats (Bania et al 2003) and humans (LeTourneau et al 2008) and the present data extend these findings to suggest a withdrawal syndrome after ten daily injections of 500 mg/kg GHB to rats. The increased social anxiety seen after abrupt discontinuation of GHB treatment is reminiscent of that seen in rats undergoing either ethanol (Knapp et al 2007) or benzodiazepine (File et al 1991) withdrawal, and consistent with there being some similarity in the neuroadaptations caused by these compounds on brain GABAergic systems. Interestingly, this withdrawal effect was not seen in rats given the MDMA/GHB combination, suggesting an amelioration of acute GHB withdrawal when coadministered with MDMA.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, numerous reports have shown that withdrawal from chronic intermittent EtOH exposure results in pronounced increases in anxiety-like behaviors (for review see Kliethermes, 2005;McCool et al, 2010). In addition, cycles of chronic stress can substitute for cycles of chronic intermittent EtOH exposure (Knapp et al, 2007). Therefore, it also seems possible that chronic EtOH exposure may disrupt inhibitory effects of NE in the BLA and thus contribute to the progressive increase in anxiety associated with alcohol abuse disorders.…”
Section: ␤1-ars Mediate Etoh Enhancement Of Lpcs Gabaergic Synapses 457mentioning
confidence: 99%
“…Furthermore, administration of baclofen has been reported to inhibit the severity of the alcohol withdrawal syndrome (AWS), including anxiety-related behaviors, tremors, and seizures in rats made physically dependent on alcohol Knapp et al, 2007). Different lines of experimental evidence suggest that mesolimbic DA neurons are involved in the mediation of alcohol intake and reinforcement (Weiss and Porrino, 2002;Melis et al, 2005).…”
Section: Baclofenmentioning
confidence: 99%
“…Preclinical data showed that baclofen reduces the severity of AWS in rats made physically dependent on alcohol Knapp et al, 2007). On the basis of preliminary promising results in humans (Addolorato et al, 2002), a randomized study compared baclofen (10 mg t.id.…”
Section: Baclofenmentioning
confidence: 99%